2021
DOI: 10.21037/atm-20-3487
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery disease: differential expression of ceRNAs and interaction analyses

Abstract: Background: Previous studies have demonstrated associations between cardiovascular disease and the expression of various messenger RNAs (mRNAs), microRNAs (miRNAs), and long non-coding RNAs (lncRNAs). This study aimed to investigate the differential expression of mRNAs, lncRNAs, and miRNAs between tissues from patients with coronary artery disease (CAD) and healthy controls, and to determine the interactions between these molecules in CAD.Methods: We investigated the differential expression of competitive endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…We identified two core microRNAs (miR-466i-5p and miR-574-5p) in the microRNA-mRNA co-expression network that predicted the association between microRNA and target genes in MI + CIH heart tissue, and these were also associated with the PI3K-Akt signaling pathway. Indeed, several studies have shown that lncRNAs can act as ceRNAs that sequester miRNAs, thus allowing for de-repression of downstream miRNA targets (Wang et al, 2019;Kang et al, 2021). Such integration between coding and non-coding RNA forms complex ceRNA networks that when dysregulated lead to cardiac remodeling after MI (Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified two core microRNAs (miR-466i-5p and miR-574-5p) in the microRNA-mRNA co-expression network that predicted the association between microRNA and target genes in MI + CIH heart tissue, and these were also associated with the PI3K-Akt signaling pathway. Indeed, several studies have shown that lncRNAs can act as ceRNAs that sequester miRNAs, thus allowing for de-repression of downstream miRNA targets (Wang et al, 2019;Kang et al, 2021). Such integration between coding and non-coding RNA forms complex ceRNA networks that when dysregulated lead to cardiac remodeling after MI (Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have shown that lncRNAs can act as ceRNAs that sequester miRNAs, thus allowing for de-repression of downstream miRNA targets ( Wang et al, 2019 ; Kang et al, 2021 ). Such integration between coding and non-coding RNA forms complex ceRNA networks that when dysregulated lead to cardiac remodeling after MI( Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of MEG3 decreased the expression of miR-145, which in turn increased the expression of the target gene PDCD4 and promoted cardiomyocyte apoptosis (5). Recently, despite a ceRNA literature report on CAD, it revealed 11 pathways and 15 key genes related to CAD, which provided options for the treatment of CAD (6). However, our study used different datasets from the previous ones.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs can regulate pathological mechanisms and disease progression through different target genes or signaling pathways, making them essential biomarkers [ 6 ]. LncRNAs, a non-coding RNA larger than 200 nucleotides, play a biological role in CAD by acting on downstream target molecules such as microRNAs (miRNAs, miRs), mRNAs, or transcription factors [ 7 , 8 ]. Most lncRNAs act as competing endogenous RNAs (ceRNAs) and regulate the expression and activation of downstream mRNAs by competitive binding with miRNAs, thus affecting the cardiovascular system’s biological functions, such as cell proliferation, migration, and apoptosis.…”
Section: Introductionmentioning
confidence: 99%